The fault in our land impact of proximity to West Valley Fault and earthquake information on land valuation in Quezon City - Sibal, Clarisse Kora L.; Tuazon, Alyya Amerys A.; Magno, Cielo D. (Quezon City School of Economics, University of the Philippines Diliman, 2018)
The Philippines, being located at the Pacific Ring of Fire, is at high risk of earthquakes. Geologists have predicted that the West Valley Fault is due to cause a 7.3_magnitude earthquake in the near future. With this, we analyze the impact of proximity to the West Valley Fault and earthquake risk awareness on land valuation in Quezon City on land valuation in Quezon City. Using a cross_sectional dataset of Quezon City properties bought in 2016 and a hedonic pricing model, we estimate the effects of the distance from the West Valley Fault and awareness of the dangers of earthquakes using earthquake drill dates as proxy variable on price per square meter of land. Results show that land prices are indeed significantly lower when nearer to the fault, and whose purchase dates are farther from earthquake drill dates. The results of this study may be helpful to the government in promoting awareness and safety of the Filipino community against earthquakes.
Thesis (B.S. Business Economics) -- University of the Philippines Diliman
Keywords: Real property -- Valuation -- Philippines -- Quezon City; Earthquake zones -- Economic aspects -- Philippines -- Quezon City; Marikina Valley Fault System -- West Valley Fault